A novel biomedical titanium alloy with high antibacterial property and low elastic modulus. (10th August 2021) - Cai, Diangeng; Zhao, Xiaotong; Yang, Lei; Wang, Renxian; Qin, Gaowu; Chen, Da-fu; Zhang, Erlin
Abstract: β-type titanium alloys have attracted much attention as implant materials because of their low elastic modulus and high strength, which is closer to human bones and can avoid the problem of stress fielding and extend the lifetime of prosthetics. However, other issues, such as the infection or inflammation postimplantation, still trouble the titanium alloy's clinical application. In this paper, we developed a novel near β-titanium alloy (Ti-13Nb-13Zr-13Ag, TNZA) with low elastic modulus and strong antibacterial ability by the addition of Ag element followed by proper microstructure controlling, which could reduce the stress shielding and bacterial infections simultaneously. The microstructure, mechanical properties, corrosion resistance, antibacterial properties and cell toxicity were studied using SEM, electrochemical testing, mechanical test and cell tests. The results have demonstrated that TNZA alloy exhibited an elastic modulus of 75−87 GPa and a strong antibacterial ability (up to 98 % reduction) and good biocompatibility. Moreover, it was also shown that this alloy's corrosion resistance was better than that of Ti-13Nb-13Zr. All the results suggested that Ti-13Nb-13Zr-13Ag might be a competitive biomedical titanium alloy.